Polycyclic aromatic hydrocarbons in Ethiopian soils: Distribution, sources, and implication from energy consumption structures - Xinyue Shan; Wang Yuan; Shuai Song; Qiang Wu; Fadong Li; Gang Chen; Shengjie Yang; Chao Su; Hubert Hirwa (Emerging Contaminants)
Polycyclic aromatic hydrocarbons (PAHs), a ubiquitous substance in the environment, are closely associated with human energy consumption, which can be released to the environment from incomplete biomass combustion or emitted from petroleum. There is currently a knowledge gap on the relationships between energy consumption structures (ECSs) and PAH contamination, especially in African countries. This study investigated the distribution, sources, and risks of 16 prioritized PAH compounds (Σ16PAHs) in Ethiopian soils, and explored the impact of ECSs on PAH contamination. The concentrations of Σ16PAHs ranged from 12.51 to 435.67 ng/g, descending across an urban-rural gradient. Based on diagnostic ratios and positive matrix factorization (PMF) model, biomass combustion was the most important source. By comparing the ECSs and PAH concentrations in African countries, it was found that differences in ECSs shaped the diverse patterns of sources and concentrations of PAHs in Africa. The results of incremental lifetime cancer risk assessment suggested PAHs posed a low risk to children, adolescents, and adults. The Ethiopian government has been making continuous efforts to develop cleaner energy and optimize ECSs to decrease soil PAH concentrations and reduce potential risks. This study will provide support for Ethiopia to improve energy structure management.